Environmental, social and governance factors in companies’ business models and the motives of incorporated them in the core business - Bak, Iwona; Ziolo, Magdalena; Cheba, Katarzyna; Spoz, Anna (Journal of Business Economics and Management, 2022)
The aim of the article is to study ESG factors and the motives of including the ESG perspective by companies in their business models (BM). The 2-stage research procedure was used to analyse the problem: bibliographic research was carried out with the use of VOSviewer software. In the paper, 99 from 3000 publications were selected for in-depth analyses, and various types of correlation measures were selected, examining the strength and direction of the relationship between the variables included in two-way and multi-way frequency tables. Fourteen binary variables were constructed with two categories, “yes” and “no”, which were assigned ranks 1 and 0, respectively. It turned out that there is a moderate (0.379) significant correlation between ESG factors and companies’ business models. The environmental factor is most often emphasized in these models (0.308). In the SME sector, CSR (1.000 – full correlation) and ESG factors (0.471) are taken into account, with the strongest relationships between this sector and Government (0.615) and Social (0.549). The role of the financial market in supporting sustainability in companies’ business models is growing and taking on importance.First published online 01 March 2022